2017
DOI: 10.1093/nar/gkx115
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a novel biophysical model using large scale in vivo antisense hybridization data displays improved prediction capabilities of structurally accessible RNA regions

Abstract: Current approaches to design efficient antisense RNAs (asRNAs) rely primarily on a thermodynamic understanding of RNA–RNA interactions. However, these approaches depend on structure predictions and have limited accuracy, arguably due to overlooking important cellular environment factors. In this work, we develop a biophysical model to describe asRNA–RNA hybridization that incorporates in vivo factors using large-scale experimental hybridization data for three model RNAs: a group I intron, CsrB and a tRNA. A un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 91 publications
(133 reference statements)
0
28
0
Order By: Relevance
“…As shown in Figures 4E,F, Zms4 and Zms6 contain multiple functional sites that potentially contribute to multi-tasking in their function. Moreover, these sites are predicted to occupy regions of high and low hybridization efficacy, as identified by the InTherAcc biophysical model (Vazquez-Anderson et al, 2017), which could explain the observed differences in binding affinities. These results also imply that Zms4 and Zms6 could bind and regulate multiple targets simultaneously and efficiently.…”
Section: Confirmation Of Multiple Direct Rna Targetsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Figures 4E,F, Zms4 and Zms6 contain multiple functional sites that potentially contribute to multi-tasking in their function. Moreover, these sites are predicted to occupy regions of high and low hybridization efficacy, as identified by the InTherAcc biophysical model (Vazquez-Anderson et al, 2017), which could explain the observed differences in binding affinities. These results also imply that Zms4 and Zms6 could bind and regulate multiple targets simultaneously and efficiently.…”
Section: Confirmation Of Multiple Direct Rna Targetsmentioning
confidence: 96%
“…Ultimately, electrophoretic mobility shift assays (EMSAs) and reporter gene systems can complement these approaches in testing direct binding of RNA and protein targets in vitro and in vivo (Corcoran et al, 2012;Tomasini et al, 2017). Most recent, the mapping of sRNA interfaces that could be available in vivo for interactions has also been useful to determine biologically relevant mRNA targets (Vazquez-Anderson et al, 2017;Mihailovic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in vivo chemical and enzymatic probing methods gauge the level of “protection” or reactivity of individual bases/backbones within a region of interest, and have recently been adapted for high-throughput use 26 , 27 . As these local nucleotide availabilities do not always correlate with regional-level accessibility that more accurately mimics RNA:RNA interactions of regulatory interfaces 28 , efforts have also been placed on methods to quantify regional in vivo RNA hybridization. Corresponding datasets have yielded useful predictions of regions capable of establishing RNA:RNA interactions 28 .…”
Section: Introductionmentioning
confidence: 99%
“…As these local nucleotide availabilities do not always correlate with regional-level accessibility that more accurately mimics RNA:RNA interactions of regulatory interfaces 28 , efforts have also been placed on methods to quantify regional in vivo RNA hybridization. Corresponding datasets have yielded useful predictions of regions capable of establishing RNA:RNA interactions 28 . Nonetheless, acquisition of these data is typically limited by low-throughput experiments 28 , 29 and reliance on sRNA overexpression that disturbs native transcript or protein stoichiometry 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation